Implementation of Best Practices Regarding Treatment Fidelity in the Family Colorectal Cancer Awareness and Risk Education Randomized Controlled Trial. (18th November 2014) - Simmons, Rebecca G.; Walters, Scott T.; Pappas, Lisa M.; Boucher, Kenneth M.; Boonyasiriwat, Watcharaporn; Gammon, Amanda; Vernon, Sally W.; Burt, Randall M.; Stroup, Antoinette M.; Kinney, Anita Y.
Treatment fidelity is associated with improvement in research outcomes and increased confidence in significant findings. However, few studies report on recommended areas of treatment fidelity (i.e., study design, training, treatment delivery, treatment receipt, and treatment enactment), leaving a dearth of information about implementation components that contributed to a study's success. Without such information, it is difficult for researchers to correctly assess previous findings and for practitioners to correctly implement findings into practice. Thus, it is crucial that studies assess both treatment fidelity and applicability of treatment fidelity findings. We report measures of treatment fidelity in a randomized controlled trial of an intervention promoting colonoscopy in at-risk relatives of colorectal cancer (CRC) patients. We describe assessments related to both treatment delivery and treatment receipt. We conducted separate ANCOVAs to model the change in each of the treatment receipt variables, comparing the two intervention arms. Compared with the control group, the intervention group had significantly greater improvements in CRC knowledge ( f = 17.46, p < .0001), perceptions about susceptibility ( f = 15.08, p = .0002), response efficacy ( f = 7.46, p = .0076), self-efficacy ( f = 8.16, p = .0053), and reduced decisional uncertainty ( f = 19.59, p < .0001) from baseline to 1-month follow-up. Overall, our study adhered to most of the best-practice guidelines for behavioral intervention fidelity. This demonstrates that our intervention was delivered as intended and positively affected the cognitive processes that are purported to be predictive of adherent behavioral outcomes.